Accounting Education to Strengthen the Governance of Micro, Small and Medium Enterprises in Kembangan Sub-district - Chairunisa, Mariyam; Nurhasanah, Nurhasanah (Transpublika Publisher, 2025)
Micro, Small and Medium Enterprises (MSMEs) are resilient and resistant to economic crises and are able to absorb labor so that they can reduce unemployment. MSMEs need activities that can help them realize good governance so that they can run their businesses sustainably. One of the needs for these activities is an activity in the form of education regarding accounting records that can help them understand the importance of separating business finances and personal finances. The purpose of implementing community service activities in Accounting Recording Education to Strengthen MSME Governance in Kembangan District, West Jakarta is to provide education and assistance to MSMEs regarding accounting records and their benefits for business sustainability and to help MSMEs implement bookkeeping in their daily activities. This service activity is intended so that MSMEs in Kembangan District, West Jakarta can understand good governance through accounting records so that it is easier for them to develop their performance and know the development of their business through simple accounting records in the form of recording incoming and outgoing cash flows.